The sources and prevalence of anthropogenic noise in Rockfish Conservation Areas with implications for marine reserve planning. (March 2021) - Nikolich, Katrina; Halliday, William D.; Pine, Matthew K.; Cox, Kieran; Black, Morgan; Morris, Corey; Juanes, Francis
Abstract: Underwater noise pollution is a recognized threat to marine life. In British Columbia, Canada, Pacific rockfish ( Sebastes spp.) were historically overfished, prompting the establishment of Rockfish Conservation Areas (RCAs). However, there are no restrictions prohibiting vessel transits in RCAs. We hypothesized that RCAs do not protect rockfish from sub-lethal harm from noise. We compared noise levels at three RCAs with adjacent unprotected reference sites from August 2018–June 2019. While RCAs had lower levels of noise overall than reference sites, this trend was inconsistent; some RCA sites had higher levels of noise during certain time periods than non-RCA sites. A vessel noise detector was the best predictor of noise level over three frequency bands (20–100 Hz, 100–1000 Hz, 1–10 kHz), and predicted sound levels which could mask rockfish communication. We conclude that RCAs do not reliably protect rockfish from noise pollution, and recommend further study into potential impacts on stock recovery. Highlights: Rockfish Conservation Areas protect rockfish from fishing, but not other stressors. We compared underwater noise in Rockfish Conservation Areas and reference sites. Rockfish Conservation Areas had similar underwater noise levels to reference sites. Motor vessels were important sources of noise in both protected and reference sites. Underwater noise frequently exceeded a level which may mask rockfish communication.